Hubungan Tradisi Munjung dengan Sikap Keagamaan Masyarakat Desa Panjalin Lor Kecamatan Sumberjaya Kabupaten Majalengka - Somantri Somantri (Lembaga Penerbitan dan Publikasi Ilmiah IAI Bunga Bangsa Cirebon, 2020)
The relationship between Munjung's radiation and religious attitudes fosters the strengthening of local character and traditions of the community. The aspect studied is the existence of Munjung as a strengthening of local character and traditions in Panjalin Lor Village, Sumberjaya District, Majalengka Regency. Qualitative research is chosen as a method for exploring and understanding meanings ascribed to social or humanitarian problems, focusing on individual meanings, and translating the complexity of a problem. Descriptive data is developed from the results of obtaining a number of written and oral information from observations. Munjung as a tradition and culture for the residents of Panjalin Lor becomes the spirit of a religious attitude by not seeing that Munjung is a form of denial of religious practice (Islam) which will still be done because as a form of cultural ngarumat, maintaining a good tradition to remember the struggles of the old grandmothers. serve the community as well as maintain and maintain togetherness among the villagers of Panjalin Lor as Sundanese who are influenced by the fighting motto of the Sundanese people, namely;